Volatile organic compounds produced by the phytopathogenic bacterium Xanthomonas campestris pv. vesicatoria 85-10 - Weise, Teresa; Kai, Marco; Gummesson, Anja; Troeger, Armin; von Reuß, Stephan; Piepenborn, Silvia; Kosterka, Francine; Sklorz, Martin; Zimmermann, Ralf; Francke, Wittko; Piechulla, Birgit (Beilstein Journal of Organic Chemistry, 2012)
Xanthomonas campestris is a phytopathogenic bacterium and causes many diseases of agricultural relevance. Volatiles were shown to be important in inter- and intraorganismic attraction and defense reactions. Recently it became apparent that also bacteria emit a plethora of volatiles, which influence other organisms such as invertebrates, plants and fungi. As a first step to study volatile-based bacterial–plant interactions, the emission profile of Xanthomonas c. pv. vesicatoria 85-10 was determined by using GC/MS and PTR–MS techniques. More than 50 compounds were emitted by this species, the majority comprising ketones and methylketones. The structure of the dominant compound, 10-methylundecan-2-one, was assigned on the basis of its analytical data, obtained by GC/MS and verified by comparison of these data with those of a synthetic reference sample. Application of commercially available decan-2-one, undecan-2-one, dodecan-2-one, and the newly synthesized 10-methylundecan-2-one in bi-partite Petri dish bioassays revealed growth promotions in low quantities (0.01 to 10 μmol), whereas decan-2-one at 100 μmol caused growth inhibitions of the fungus Rhizoctonia solani. Volatile emission profiles of the bacteria were different for growth on media (nutrient broth) with or without glucose.
Keywords: Aspergillus nidulans; Fusarium solani; growth inhibition and promotion; methylketones; 10-methylundecan-2-one; Rhizoctonia solani; volatile organic compound (VOC); Xanthomonas campestris pv. vesicatoria